2004
DOI: 10.1083/jcb.200405053
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of DCC by Fyn mediates Netrin-1 signaling in growth cone guidance

Abstract: Netrin-1 acts as a chemoattractant molecule to guide commissural neurons (CN) toward the floor plate by interacting with the receptor deleted in colorectal cancer (DCC). The molecular mechanisms underlying Netrin-1–DCC signaling are still poorly characterized. Here, we show that DCC is phosphorylated in vivo on tyrosine residues in response to Netrin-1 stimulation of CN and that the Src family kinase inhibitors PP2 and SU6656 block both Netrin-1–dependent phosphorylation of DCC and axon outgrowth. PP2 also blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
106
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(113 citation statements)
references
References 42 publications
7
106
0
Order By: Relevance
“…This is suggested by a similar time course of induction of both DCC and PLC␥ tyrosine phosphorylation and PIP 2 hydrolysis upon netrin-1 stimulation, an attenuation of netrin-1-induced PIP 2 hydrolysis in DCC-Y1420F-expressing cells, and an inhibition of neurite outgrowth by a PLC inhibitor. These observations are consistent with previous studies showing that DCC tyrosine phosphorylation contributes to netrin-1-induced neurite outgrowth (41), that PLC␥ signaling is required in nerve growth factor-and netrin-1-induced growth cone guidance of Xenopus spinal neurons (27), and that IP 3 receptor-mediated calcium release from intracellular stores plays an important role in axonal extension of chick dorsal root ganglia (42).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is suggested by a similar time course of induction of both DCC and PLC␥ tyrosine phosphorylation and PIP 2 hydrolysis upon netrin-1 stimulation, an attenuation of netrin-1-induced PIP 2 hydrolysis in DCC-Y1420F-expressing cells, and an inhibition of neurite outgrowth by a PLC inhibitor. These observations are consistent with previous studies showing that DCC tyrosine phosphorylation contributes to netrin-1-induced neurite outgrowth (41), that PLC␥ signaling is required in nerve growth factor-and netrin-1-induced growth cone guidance of Xenopus spinal neurons (27), and that IP 3 receptor-mediated calcium release from intracellular stores plays an important role in axonal extension of chick dorsal root ganglia (42).…”
Section: Discussionsupporting
confidence: 82%
“…In aggregate, our results suggest that neither P3 domain-mediated dimerization nor P3-FAK binding appeared to be required for netrin-1 induction of PLC signaling, thus implicating an involvement of other P3-dependent-binding proteins in this event. DCC has been found to be phosphorylated at tyrosine 1420 (Tyr 1420 ), a site close to the P3 region and implicated in netrin-1 signaling (19,41). We thus examined whether DCC-Tyr 1420 phosphorylation contributes to netrin-1-induced PIP 2 hydrolysis.…”
Section: Independence Of Dcc-p3 Homodimerization or Fak For Netrin-1-mentioning
confidence: 99%
“…However, the finding that the enhancement of neurite outgrowth induced by ␤-cyclodextrin treatment is accompanied by the recruitment of Fyn to lipid rafts and that the Src family inhibitor PP2 inhibits axonal elongation induced by ␤-cyclodextrin treatment suggests that an increased level of raft-localized Fyn is in part involved in ␤-cyclodextrin-induced axonal elongation in hippocampal neurons. This notion is supported by previous studies showing that Src family kinases, including Fyn, play a critical role in axon outgrowth (27,28) and that lipid raft-localized Fyn is more catabolically active than non-raft-localized Fyn (29,30).…”
Section: Discussionsupporting
confidence: 76%
“…It has been shown that netrin-1 induces tyrosine phosphorylation of DCC in commissural neurons and that this phosphorylation is crucial for netrin-1-dependent axon outgrowth function (Meriane et al, 2004). To analyze DCC phosphorylation, HEK293T cells transfected with myc-tagged DCC were treated with netrin-1.…”
Section: Effect Of the Abrogation Of Hs Expression On Netrin-1 Downstmentioning
confidence: 99%